Severe Heterotopic Ossification with Proximal Entrapment of the Ulnar Nerve following Primary Anterior Shoulder Dislocation - Malik Jessen; Christian Gerhardt; Lars-Johannes Lehmann; Jonas Schmalzl (Case Reports in Orthopedics)
Heterotopic ossifications (HO) in the shoulder are rare. The effectiveness of conservative treatment is limited, and therefore, symptomatic cases are usually treated surgically. However, there are no guidelines for the surgical treatment of HO. Herein, we report the case of a 45-year-old man with severe HO and proximal entrapment of the ulnar nerve following primary anterior shoulder dislocation without concomitant injuries (e.g., fracture and rotator cuff tears). Surgical intervention was indicated, including resection of HO and neurolysis of the brachial plexus. Nine months after surgery, the patient presented with restored shoulder function, pain relief, and good patient satisfaction. The case shows that the ulnar nerve can also be impaired due to HO following shoulder dislocation.